Variable Patterning of Chromatin Remodeling, Telomere Positioning, Synapsis, and Chiasma Formation of Individual Rye Chromosomes in Meiosis of Wheat-Rye Additions - Naranjo, Tomás (Frontiers in Plant Science, 2018)
Meiosis, the type of cell division that halves the chromosome number, shows a considerable degree of diversity among species. Unravelling molecular mechanisms of the meiotic machinery has been mainly based on meiotic mutants, where the effects of a change were assessed on chromosomes of the particular species. An alternative approach is to study the meiotic behavior of the chromosomes introgressed into different genetic backgrounds. As an allohexaploid, common wheat tolerates introgression of chromosomes from related species, such as rye. The behavior of individual pairs of rye homologues added to wheat has been monitored in meiotic prophase I and metaphase I. Chromosome 4R increased its length in early prophase I much more than other chromosomes studied, implying chromosome specific patterns of chromatin organization. Chromosome conformation affected clustering of telomeres but not their dispersion. Telomeres of the short arm of submetacentric chromosomes 4R, 5R and 6R failed more often to be included in the telomere cluster either than the telomeres of the long arms or telomeres of metacentrics such as 2R, 3R and 7R. The disturbed migration of the telomeres of 5RS and 6RS was associated with failure of synapsis and chiasma formation. However, despite the failed convergence of its telomere, the 4RS arm developed normal synapsis, perhaps because the strong increase of its length in early prophase I facilitated homologous encounters in intercalary regions. Surprisingly, chiasma frequencies in both arms of 4R were reduced. Similarly, the short arm of metacentric chromosome 2R often failed to form chiasmata despite normal synapsis. Chromosomes 1R, 3R and 7R showed a regular meiotic behavior. These observations are discussed in the context of the behavior that these chromosomes show in rye itself.